Análise evolutiva e ecológica da relação parasita-hospedeiro em Monogenea (Platyhelminthes) parasitas de peixes - Capparros, Eloiza Muniz (2015)
Monogenetic are mostly ectoparasites found mainly in fish and with monoxenic life cycle. They are considered highly specific to their hosts. However, some species can parasitize more than one host species, without morphology or physiology modification. To analyze ecological and evolutionary relationships established between monogenetic and their hosts, this study was divided into two parts: first, consists in a study on the state of the art about evolutionary parasitology in freshwater fish; second is an ecological and evolutionary study of the relationships between parasites and hosts. Were considered here four fish species, all belonging to the subfamily Tetragonopterinae (Characiformes: Characidae): Astyanax altiparanae, Moenkhausia dichroura, M. forestii and M. aff. intermedia. The parasites found in two different species were analyzed, recorded and reported. Among those found Monogenetic, it is proposed three new species of Jainus (Ancyrocephalinae: Dactylogyridae), a new species of Gyrodactylus sp. (Gyrodactylidae) and a new recorded of Anacanthocotyle anacanthocotyle (Isancistrinae: Gyrodactylidae). Thus, the relationships that each species of parasite establishes with their hosts were analyzed; Jainus species are highly specific as to the host; Gyrodactylus spp. and A. anacanthocotyle are also specific but greater ecological fitting or adaptability to a new host, although phylogenetically close to the original host.